EFL interaction in face-to-face versus synchronous computer-mediated communication settings: A post-secondary mixed methods study (Pädagogische Horizonte, 2024)
Interaction, a central construct in EFL teaching (Huth, 2021), has gained momentum in post-COVID online interactional contexts, in particular for face-to-face (FTF) versus synchronous computer mediated communication (SCMC, Aubrey & Philpott, 2023; Berglund, 2009; Kim, 2014; Loewen & Sato, 2018; Ziegler, 2016; Zou & Jin, 2021). The present exploratory study investigated these two contexts with regard to the interactional components willingness to communicate (WTC), communicative self-confidence (CSC), and frequency of language use (FE) in Austrian student teachers, partly replicating Darasawang and Reinders (2021). Using a parallel convergent mixed-methods design (Creswell & Plano Clark, 2006), quantitative and qualitative data were collected from 58 student teachers after exposure to both contexts in two CLIL-based courses. An online survey with 21 items explored in how far interactional context affected WTC, CSC, and FE quantitatively. The qualitative study, using two open questions for each component, explored students’ perceptions and explanations of potential interactional differences. Quantitative data were analysed using cumulative link mixed models, qualitative data underwent computer-assisted (MAXQDA) content analysis. Data triangulation revealed partly inconsistent results. On the one hand, there were overall negative effects for SCMC, with explanations including contextual and linguistic factors for CSC and pedagogical reasons for FE. Likewise, students reported higher WTC in FTF, and argued for this with interactional and technology-related reasons. On the other hand, CSC remained inconclusive as to its anxiety component. We interpreted these results with regard to current challenges of post-COVID EFL teacher education in Austria.
Keywords: EFL teacher education; willingness to communicate; perceived communicative self-confidence; language anxiety; frequency of English use